FAKTOR PENYEBAB PERUBAHAN TRADISI NGERES RUMAH MASYARAKAT JAWA DI DESA RAWANG SARI KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN - Suwartini Suwartini; Sri Erlinda; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by a change in procedures for building a Javanese traditional house in Rawang Sari Village, Pangkalan Lesung District, Pelalawan Regency. The formulation of the problem in this study is "What are the factors that cause changes in the tradition ngeres of home in Java Rawang Sari District, Pangkalan Lesung, Pelalawan Regency. The purpose of this study is to determine what factors are causing changes in the tradition Ngeres of home in Rawang Sari Village, Pangkalan Lesung District, Pelalawan Regency. Data collection techniques in this research are observation, interview, and documentation. The research respondents chose informants namely 5 people, 1 community figure, 1 Elder (elder) and 2 community people. Data analysis techniques in this study used qualitative methods. The results in this study are that there are 2 factors causing changes in the Ngeres tradition of home in Javanese Rawang Sari Village, Pangkalan Lesung Subdistrict, Pelalawan Regency, namely the first internal factor is the mindset of people who are dissatisfied with long-standing patterns, local people who want to adjust the development of the times, the second is the advancement of public education that makes people think more logically and rationally, the third is the invention of technology, the fourth is the conflict (conflict). And external factors are those that come into contact with foreign cultures, through inter-tribal cross-marriages and diffusion.Key Words : Factors That Cause Change, Ngeres Rumah Tradition